1996
DOI: 10.1016/0248-4900(96)84781-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of internalization and subcellular binding sites for T3 in mouse liver

Abstract: The intracellular fate of radiolabeled T3 taken up by mice hepatocytes in vivo was determined at specific time intervals (2-120 min) after injection by quantitative electron microscopic radioautography. Injection of a 200-fold excess of unlabeled T3 together with [125I]-T3 resulted in a more than 90% inhibition of radioactivity detected in hepatocytes. A simple grain density (GD) analysis of radioautograms revealed that a specific labeling (GD > 1) was displayed by only five cell compartments: the plasma membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
2
9
0
Order By: Relevance
“…These data indicate that, like mt-TFA, p43 induced a strong increase in the levels of mitochondrial precursor transcripts in the presence of exogenous T3. A reduced p43 influence was observed in the absence of exogenous T3, in agreement with the fact that mitochondria are a major compartment of T3 accumulation in the cell (32,49). In addition, all of the precursor transcripts induced by p43 or mt-TFA were also detected in Northern blots performed with other mitochondrial probes (Cytb, ND 5, ND 4, ATPase 6/COX II, ND 6L, COX I, ND 2, or ND 1; Fig.…”
Section: Resultssupporting
confidence: 71%
“…These data indicate that, like mt-TFA, p43 induced a strong increase in the levels of mitochondrial precursor transcripts in the presence of exogenous T3. A reduced p43 influence was observed in the absence of exogenous T3, in agreement with the fact that mitochondria are a major compartment of T3 accumulation in the cell (32,49). In addition, all of the precursor transcripts induced by p43 or mt-TFA were also detected in Northern blots performed with other mitochondrial probes (Cytb, ND 5, ND 4, ATPase 6/COX II, ND 6L, COX I, ND 2, or ND 1; Fig.…”
Section: Resultssupporting
confidence: 71%
“…Rapidity, refractoriness to inhibitors of protein synthesis, and occurrence in the absence of nuclei ruled out the involvement of the T3 genomic pathway. Parallel to this, several studies have demonstrated that the mitochondrion is a major compartment of T3 accumulation in the cell (Palacios-Romero & Mowbray 1979, Sterling et al 1984b, Hashizume et al 1986, Morel et al 1996. These data led to the proposition that ANT was a major T3 target involved in the short-term influence of the hormone on the organelle.…”
Section: Short-term Influencementioning
confidence: 94%
“…Further, a specific mitochondrial receptor for T3 has still not been identified. Quite recently, however, the existence of specific mitochondrial binding sites for T3 has received additional confirmation from the work of Morel et al [40] and Wrutniak et al [36].…”
Section: Non‐nuclear Action Of Iodothyronines: the Direct Mitochondrimentioning
confidence: 97%
“…Morel et al [40] studied the kinetics of the internalization and specific subcellular binding of T3 in mouse liver both in vivo and in vitro. These authors showed by quantitative electron microscopy autoradiography that, after the injection of radiolabelled T3, specific binding was displayed by five cell compartments (including mitochondria).…”
Section: Non‐nuclear Action Of Iodothyronines: the Direct Mitochondrimentioning
confidence: 99%